Molecular Mechanisms of Polybrominated Diphenyl Ethers (BDE-47, BDE-100, and BDE-153) in Human Breast Cancer Cells and Patient-Derived Xenografts. (23rd February 2019) - Kanaya, Noriko; Bernal, Lauren; Chang, Gregory; Yamamoto, Takuro; Nguyen, Duc; Wang, Yuan-Zhong; Park, June-Soo; Warden, Charles; Wang, Jinhui; Wu, Xiwei; Synold, Timothy; Rakoff, Michele; et al.
Abstract: Polybrominated diphenyl ethers (PBDEs) have been used as flame retardants in household materials. Their environmental persistence has led to continuous human exposure and significant tissue levels. Three PBDE congeners (BDE-47, BDE-100, and BDE-153) have been frequently detected in human serum. Although these compounds appear to possess endocrine disrupting activity, studies are largely missing to determine the biological mechanisms of PBDEs in breast cancer cells. Here, we assessed PBDE bioactivities with three complementary strategies: receptor binding/activity assays; nonbiased RNA-sequencing analysis using an estrogen-dependent breast cancer cell line MCF-7aroERE; and in vivo assessments using patient-derived xenograft (PDX) models of human breast cancer. According to the results from in vitro experiments, the PBDE congeners regulate distinct nuclear receptor signaling pathways. BDE-47 acts as a weak agonist of both estrogen receptor α (ERα) and estrogen-related receptor α (ERRα); it could stimulate proliferation of MCF-7aroERE and induced expression of ER-regulated genes (including cell cycle genes). BDE-153 was found to act as a weak antagonist of ERα. BDE-100 could act as (1) an agonist of aryl hydrocarbon receptor (AhR), inducing expression of CYP1A1 and CYP1B1 and (2) as a very weak agonist/antagonist of ERα. In vivo, a mixture of the three congeners with ratios detected in human serum was tested in an ER+ PDX model. The mixture exhibited estrogenic activity through apoptosis/cell cycle regulation and increased the expression of a proliferation marker, Ki-67. These results advance our understanding of the mechanisms of PBDE exposure in breast cancer cells.